Functional Analysis of Natural Polyphenols and Saponins as Alternative Medicines - Sakagami, Hiroshi; Kushida, Tatsuya; Makino, Toru; Hatano, Tsutomu; Shirataki, Yoshiaki; Matsuta, Tomohiko; Matsuo, Yukiko; Mimaki, Yoshihiro (IntechOpen, 2012)
None